Entitlement to the rights of aboriginal people. - Gagné, Jocelyn. (University of Ottawa (Canada), 1992)
The question that I consider, in my thesis, is who is entitled to share in whatever distinct rights aboriginal peoples may be afforded by Canadian law. The conclusion that I reach is that only groups which are capable of exercising collective rights and which are connected, by some degree of descent, to aboriginal groups that existed prior to the coming of the Europeans are entitled to aboriginal rights today. This conclusion is derived from a consideration of the sources of aboriginal rights. Aboriginal rights, in the sense in which I use it, would include any rights which are unique to aboriginal people, including common law, treaty and constitutional rights. While the source of treaty rights appears to be, at least in part, the recognition of common law rights and the source of constitutional rights appears to be the recognition of both treaty and common law rights, the source of aboriginal peoples' common law rights is less clear. I consider two possible sources of common law aboriginal rights. The first is that British Colonial law recognized the continuing validity of aboriginal customary law, even after sovereignty was acquired. The second is that the common law afforded proprietary rights to those who were already in possession when the crown acquired sovereignty. The basis on which common law rights exist today in Canada has not been conclusively determined by the courts, although support for either of these sources can be found. I make no final conclusions in my thesis concerning the source or sources of common law aboriginal rights in Canada. (Abstract shortened by UMI.)
Keywords: Law.